Occurrence and Predictors of Challenging Behavior in Youth with Intellectual Disability with or without Autism. Issue 2 (3rd April 2021) - Esteves, Jeffrey; Perry, Adrienne; Spiegel, Rebecca; Weiss, Jonathan A.
ABSTRACT: Introduction : Challenging behaviors are common in individuals with developmental disabilities and pose significant challenges to their well-being and that of their families and communities. Method : We explored the occurrence and predictors of self-injurious behavior and aggressive/destructive behavior in 372 Canadian youths (aged 4–20 years) with a moderate to severe intellectual disability (ID), with or without autism. Data were collected through the Great Outcomes for Kids Impacted by Severe Developmental Disabilities (GO4KIDDS) basic survey. Results : Parent-report survey data indicated that 56% of the sample had displayed aggressive/destructive behavior and 39% self-injurious behavior over the past 2 months. Both behaviors were significantly more common in youths with ID plus autism compared to ID alone. There was an interaction between diagnosis and adaptive behavior in relation to aggressive/destructive behavior. For those with ID alone, lower adaptive functioning was predictive of aggressive/destructive behavior, whereas for those with ID plus autism, higher adaptive functioning was predictive. Conclusion : Overall, a large proportion of children in the sample were reported to engage in at least one challenging behavior. These findings highlight the importance of differential diagnosis, and an assessment of adaptive function to ascertain the prognosis of challenging behavior. Study limitations and avenues for future research are discussed.